Finger-powered electrophoretic transport of discrete droplets for portable digital microfluidics. Issue 13 (13th June 2016) - Peng, Cheng; Wang, Yide; Sungtaek Ju, Y.
Abstract : We demonstrate digital microfluidics based on finger-powered electrophoretic transport of aqueous droplets immersed in dielectric oil. The electrodes are biased by converting mechanical energy into electrical energy using an array of piezoelectric elements. Abstract : We report a finger-powered digital microfluidic device based on the electrophoretic transport of discrete droplets (EPD). An array of piezoelectric elements is connected in parallel to metal electrodes immersed in dielectric fluids. When deflected in a controlled sequence via human finger power, the piezoelectric elements charge and actuate droplets across each electrode pair through electrophoretic force. Successful droplet transportation requires the piezoelectric elements to provide both sufficient charge and voltage pulse duration. We quantify these requirements using numerical models to predict the electrical charges induced on the droplets and the corresponding electrophoretic forces. The models are experimentally validated by comparing the predicted and measured droplet translational velocities. We successfully demonstrated transport and merging of aqueous droplets over a range of droplet radii (0.6–0.9 mm). We further showed direct manipulation of body fluids, including droplets of saliva and urine, using our finger-powered EPD device. To facilitate practical implementation of multistep assays based on the approach, a hand/finger-rotated drum system with a programmable pattern of protrusions is designed to induce deflections of multiple piezoelectric elements and demonstrate programmable fluidic functions. An electrode-to-piezoelectric element connection scheme to minimize the number of piezoelectric elements necessary for a sequence of microfluidic functions is also explored. The present work establishes an engineering foundation to enable design and implementation of finger-powered portable EPD microfluidic devices.